The Fatigue Index of Swadaya Bhayangkara Volleyball After a Match - Sinulingga, Andrew Rinaldi; Nova, Andi; S, Wedi; Maesaroh, Siti; Firmansyah, Guntur (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Fatigue Index: means the rate at which power output declines for an athlete, which can provide information about the athlete's anaerobic capacity. This study aims to better understand the physical performance and fatigue index of athletes in Swadaya Bhayangkara volleyball after a match. This study analyzes the effects of acute fatigue from a mock match on physical performance variables among volleyball players. The research method is descriptive by observing, testing, and measuring, where the subjects are ten male volleyball players (age: 17.9 years; height: 175.5cm; weight: 61.4 kg). The fatigue index instrument is Repeat Sprint Ability (RSA) test. The measurement results obtained that one athlete had an excellent category of fatigue index, one athlete had a good category, average categories belonged to four athletes, and Poor categories belonged to four athletes. As a result, the Fatigue Index of Athlete Swadaya Bhayangkara volleyball has an average category.